Pelestarian Budaya Pakkacaping dalam Mendukung Ketahanan Budaya Masyarakat Suku Mandar (Studi pada Suku Mandar di Tinambung Kabupaten Polewali Mandar) - Hafid, Abdul; Sajidin, Muhammad; Yusri A.R, Muhammad; Susanti, Eni (Universitas Gadjah Mada, 2024)
The entry of the era of globalization and modernization has made Pakkacaping 's traditional culture less in demand by the public because it is considered village music, not cool and less prestigious. This makes the cultural resilience of the people of Tinambung District in Polewali Mandar Regency weaken. For this reason, efforts are needed to preserve Pakkacaping culture in order to support cultural resilience and maintain the culture of the Mandar tribe through traditional Pakkacaping arts to be sustainable and enjoyed by future generations. The purpose of this study is to analyze the efforts to preserve the Pakkacaping culture of the Mandar Tribe Community in strengthening Cultural Resilience in Tinambung District, Polewali Mandar Regency, West Sulawesi Province. The research uses a case study method with a qualitative approach with Tangnga-Tangnga Village Government informants, youth leaders, and Pakkacaping players. Data collection through primary data and secondary data. Data collection techniques include semi-structured interviews, observation and analysis of documents. Data analysis techniques are in the form of data reduction, data presentation, and conclusion drawing. The results of the study show that the Pakkacaping culture still exists and is able to be a catalyst in strengthening the cultural resilience of the Mandar Tribe community, especially in Tinambung District, Polewali Mandar Regency. Collaboration and support (budget, equipment assistance, art festivals, and others) both from the government, youth leaders and Pakkacaping art players are needed in popularizing Pakkacaping culture to the wider community. The strategy is to strengthen the resilience of Pakkacaping culture through the ability to maintain the cultural value system, adapt to changing times, integrate the community to support Pakkacaping culture and create common goals in the community regarding Pakkacaping culture. The support of various elements of society (government, cultural arts actors and youth leaders) and encouraging the four main functions of culture to develop so that Pakkacaping culture can continue to survive and not be eroded by the changing times.